IDENTIFICATION OF SERPTICAEMIA EPIZOOTICA (SE) ON SWAMP BUFFALOES (KALANG BUFALLOES) IN SOUTH KALIMANTAN - Bambang Nganji Utomo; Tarmudji Tarmudji; A. Hamdan (Jurnal Sain Veteriner, 1999)
Identification of Septicaemia Epizootica (SE) was carried out on swamp buffaloes at the districts of Hulu Sungai Tengah (HST) and Hulu Sungai Utara (HSU) and those which were slaughtered in the abbatoars of Banjarmasin, Banjarbaru and Amuntai, South Kalimantan. This study was conducted to find out whether Septicaemia Epizootica was present among the swamp buffaloes population. Thirty two samples of swab nasopharynx from the field (HSU and HST) and 60 samples from the abbatoars were collected and checked toward Pasteurella multocida. And 45 samples of sera were examined for antibody with Elisa method. Based on bacteriological examination there was no Pasteurella multocida could be identified from the samples and from Elisa examination was also negative from Septicaemia Epizootica.